High-performance yellow- and orange-emitting diodes based on novel sublimable cationic iridium(iii) complexes by ligand control. Issue 21 (16th May 2018) - Ma, Dongxin; Liu, Ruihuan; Qiu, Yong; Duan, Lian
Abstract : High-performance yellow and orange luminescence is achieved using novel sublimable cationic iridium(iii ) complexes with bulky cyclometalated ligands. Abstract : We have devised a series of novel sublimable cationic iridium(iii ) complexes by ligand control, investigated their photophysical properties, electrochemical behaviours and thermal stabilities, and then fabricated vacuum-evaporated-deposited organic light-emitting diodes. By doping these cationic iridium(iii ) complexes into a thermally activated delayed fluorescence bipolar host material at very low concentrations of 1 or 2%, we have achieved high-performance yellow- and orange-emitting diodes with peak external quantum efficiencies of 13.7 and 10.3%, respectively. All the devices show maximum luminance exceeding 27.3 × 10 3 cd m −2 and low turn-voltages varying from 2.2 to 2.5 V. To our knowledge, these values are the record performance of analogous devices based on cationic iridium(iii ) complexes, indicating their great promise as phosphorescent emitters for flat-panel displays and solid-state lightning techonology.